2016
DOI: 10.1002/hep.28704
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mast cell‐secreted histamine decreases biliary proliferation and fibrosis in primary sclerosing cholangitis Mdr2−/− mice

Abstract: Background and Aim Hepatic fibrosis is marked by activation of hepatic stellate cells (HSCs). Cholestatic injury precedes liver fibrosis and cholangiocytes interact with HSCs promoting fibrosis. Mast cells (MCs) infiltrate following liver injury and release histamine increasing biliary proliferation. We evaluated if inhibition of MC-derived histamine decreases biliary proliferation and fibrosis. Methods WT and Mdr2−/− mice (9-11 weeks) were treated with cromolyn sodium for 1 week to block MC-derived histamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
173
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(185 citation statements)
references
References 48 publications
9
173
1
Order By: Relevance
“…When BDL rats or Mdr2 –/– mice are treated with the MC stabilizer, cromolyn sodium (blocks MC HA release), biliary mass and proliferation are significantly reduced . Thus, we suspect that MCs are an important player in the regulation of biliary hyperplasia following BDL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When BDL rats or Mdr2 –/– mice are treated with the MC stabilizer, cromolyn sodium (blocks MC HA release), biliary mass and proliferation are significantly reduced . Thus, we suspect that MCs are an important player in the regulation of biliary hyperplasia following BDL.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the effects of MC deficiency on intrahepatic bile duct mass (IBDM) and proliferation in both WT and Kit W‐sh mice with sham or BDL surgery. IHC, real‐time PCR, and western blotting were performed for the biliary marker, CK‐19, to measure IBDM, and cholangiocyte proliferation was determined by Ki‐67 staining …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that inhibition of mast cell-derived histamine secretion attenuates bile duct hyperplasia during BDL in vivo [69]. Another study has shown that serum levels of histamine are increased in Mdr2 −/− mice, and inhibition of mast cell-derived histamine secretion decreases serum histamine levels as well as bile duct hyperplasia and fibrosis in these mice [70]. Mast cell-deficient mice show less liver damage, bile duct mass, and fibrosis during BDL compared to wild-type [71].…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%